If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -6 = 13 + 5x Reorder the terms: -6 + 8x = 13 + 5x Solving -6 + 8x = 13 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -6 + 8x + -5x = 13 + 5x + -5x Combine like terms: 8x + -5x = 3x -6 + 3x = 13 + 5x + -5x Combine like terms: 5x + -5x = 0 -6 + 3x = 13 + 0 -6 + 3x = 13 Add '6' to each side of the equation. -6 + 6 + 3x = 13 + 6 Combine like terms: -6 + 6 = 0 0 + 3x = 13 + 6 3x = 13 + 6 Combine like terms: 13 + 6 = 19 3x = 19 Divide each side by '3'. x = 6.333333333 Simplifying x = 6.333333333
| 21=4m+23 | | 2x=6x-8 | | 4(3+4x)=-100 | | -3(10p-5)= | | 3x-3(5x-6)= | | (-2)=2(-2) | | 100y^2-9x^2=25 | | 3.25p+4(.75p-12)=-79.25 | | 3(x-4)=10+(-1) | | 2x-10x^2=0 | | .45+Y=1.0 | | 6(4m-1)+3=-99 | | 12+2x=36+x | | 3.25p+4(.75p-12)=79.25 | | x-2x=-2 | | 26=1/5n-3 | | r-7.9=-7.3 | | X^2+(2K+1)X+K=0 | | 2(10d+13)= | | 6(3z-3)-2z-15= | | 4x-9y-6x+4y= | | 4y-3x=0 | | 3n+15=-19+2n | | -3x-8y=0 | | -5x-4=-9 | | 2e+7=15 | | 10-6x-7-9x=6 | | 8n+5=20 | | 0.50+0.10(110)=0.25(116) | | 6n+2=32 | | 0.3x+17.5=x-8.12 | | 8n-5=20 |